Modulus of Elasticity and Bending Strength of Scots Pine (Pinus sylvestris L.) Wood from Commercial Thinnings - Stöd, Reeta; Marttila, Juhani; Tomppo, Laura; Haapala, Antti; Verkasalo, Erkki (MDPI AG, 2024)
The static bending properties of Scots pine (Pinus sylvestris L.) clear wood were studied using a material collected from commercial thinning forests in eastern Finland. In Myrtillus type, the modulus of elasticity and bending strength of the first thinning wood were 7.8 GPa and 66.0 MPa, respectively, whereas for more mature wood from the second thinnings, the modulus of elasticity and bending strength were 10.0 GPa and 80.3 MPa. The results were compared with final fellings, which resulted in the modulus of elasticity of 10.1 GPa and bending strength of 81.8 MPa. The bending properties of the first thinning material were low, and thus they did not indicate any potential for applications requiring high strength or stiffness and material homogeneity. On the contrary, the properties of Scots pine wood from the second commercial thinnings may be comparable with or sometimes even better than those of the final-felling wood. The results can be utilised in wood marketing, procurement, sorting, allocation to different industries and end-uses, as well as in wood processing, product sales, and branding.
Keywords: bending strength; clear wood; harvesting; mechanical properties; modulus of elasticity; Scots pine; thinning (forestry); wood materials; wood industry; wood products